Pitch and amplitude perturbation measures in 7 year old children - Neelu Kabra (Journal of All India Institute of Speech and Hearing, 1970)
Variation in pitch and amplitude is an essential aspect of-normal voice. Theses normal variations (perturbations) in the voice can be grouped into voluntaryperturbations (intonational) and involuntary perturbations (Pitch and Amplitude Perturbations _ Jitter and Shimmer respectively).